2021
DOI: 10.3390/cryst11060581
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relations of Earth’s Core-Forming Materials

Abstract: Recent updates on phase relations of Earth’s core-forming materials, Fe alloys, as a function of pressure (P), temperature (T), and composition (X) are reviewed for the Fe, Fe-Ni, Fe-O, Fe-Si, Fe-S, Fe-C, Fe-H, Fe-Ni-Si, and Fe-Si-O systems. Thermodynamic models for these systems are highlighted where available, starting with 1 bar to high-P-T conditions. For the Fe and binary systems, the longitudinal wave velocity and density of liquid alloys are discussed and compared with the seismological observations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 190 publications
(900 reference statements)
2
6
0
Order By: Relevance
“…We conclude that in the investigated P‐T‐X range, that is, 19–35 GPa, 2100–2400 K with 0–14.8 mol% O, liquid Fe‐O alloys mix ideally regarding volume and density. In agreement with observations at 1 bar (Komabayashi, 2021) and melting experiments at higher pressures (Chen et al., 2008; Pease & Li, 2022; Pommier et al., 2018) that suggest non‐ideality for the Fe‐S system, we find that volume, density and compressibility cannot be accurately described by linear mixtures of liquid Fe and S (Figure 2 and Figure S3 in Supporting Information ). The excess molar volume of mixing for Fe‐S is taken into account in our mixing model and will be discussed below.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We conclude that in the investigated P‐T‐X range, that is, 19–35 GPa, 2100–2400 K with 0–14.8 mol% O, liquid Fe‐O alloys mix ideally regarding volume and density. In agreement with observations at 1 bar (Komabayashi, 2021) and melting experiments at higher pressures (Chen et al., 2008; Pease & Li, 2022; Pommier et al., 2018) that suggest non‐ideality for the Fe‐S system, we find that volume, density and compressibility cannot be accurately described by linear mixtures of liquid Fe and S (Figure 2 and Figure S3 in Supporting Information ). The excess molar volume of mixing for Fe‐S is taken into account in our mixing model and will be discussed below.…”
Section: Resultssupporting
confidence: 91%
“…We conclude that in the investigated P-T-X range, that is, 19-35 GPa, 2100-2400 K with 0-14.8 mol% O, liquid Fe-O alloys mix ideally regarding volume and density. In agreement with observations at 1 bar (Komabayashi, 2021) and melting experiments at Results from our ab inito molecular dynamics simulations are shown as solid circles. Experimental data for liquid Fe (K20 (Kuwayama et al, 2020) and N20 (Nishida et al, 2020)), Fe-S (B03 (Balog et al, 2003), M13 (Morard et al, 2013), K17 (Kawaguchi et al, 2017), N20 (Nishida et al, 2020) and K22 (Kawaguchi et al, 2022)) and Fe-C (N15 (Nakajima et al, 2015)) are shown as solid or open angular markers.…”
Section: Density and Incompressibilitysupporting
confidence: 88%
See 1 more Smart Citation
“…Seismological, cosmochemical, and mineral physics studies indicate that the Earth's core is mainly composed of iron with some amounts of impurities to account for a 4%-7% density deficit compared to pure iron at the relevant pressure (P) and temperature (T) conditions [1,2]. Over 70 years since the first proposition by [1], the light element in the core is yet to be determined even among a small number of candidate elements: Si, S, O, C, and H [3][4][5]. Of these candidate elements, sulphur has been most extensively studied [3] and the binary system Fe-S is currently still of significant interest [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the 10 original research articles described above, this Special Issue also include two review articles. In the first one, Tetsuya Komabayashi [11] shows an overview on the recent updates on the phase-relations in Fe-alloys as a function of pressure and temperature. Such phase-relations are of particular interest for the engineering and metallurgy fields-as they serve as recipes for creating specific phases with certain properties-and are of extreme importance for Earth science, as the major components of the Earth's core-subjected to extreme conditions of pressure and temperature-are Fe and a detailed characterisation of the phase domains of their (geophysically relevant) alloys at those extreme conditions can provide important information on the dynamics and evolution of our planet.…”
mentioning
confidence: 99%